Transforming the Quality Maternal Newborn Care Framework into an index to measure the quality of maternity care. Issue 1 (5th December 2022) - Cummins, Allison; Symon, Andrew
Abstract: Background: The Quality Maternal and Newborn Care (QMNC) Framework describes the care that childbearing women and newborn infants need in all settings. It comprises five components and was designed for use in planning, workforce development, and resource allocation, aimed at improving the quality and cost effectiveness of maternal and newborn care globally. The purpose of this paper is to describe the first phase of a project designed to transform the Framework into a quantitative tool for service user assessment of the quality of maternity care. Methods: Each component of the original Framework content was developed into a draft service user questionnaire and distributed to an expert panel, drawn from a range of low‐, middle‐, and high‐resource countries. The panel consisted of five Framework authors, nine midwife researchers, six midwives, and five service user (consumer) advocates. Two rounds of discussion and revision were undertaken with the expert panel who commented on the importance, relevance and clarity of questions, and then on their necessity, wording, and order. A third round involved two experts in survey design. Results: Following 24 responses in the first round, the questions were refined and returned to the panel. After incorporating the second‐round comments from 16 experts, the survey was then sent to two experts in questionnaire design and construction. Face validity was affirmed through this consultative process. Conclusions: Despite Covid‐19 pandemic‐related restrictions, this robust iterative consultative process with an international expert panel has resulted in the prototype QMNC Framework index (QMNCFi)—a questionnaire designed for use in diverse settings to assess the quality of maternity care. The QMNCFi's psychometric properties are now being tested in an international online survey.